Fenómenos transitorios en bifurcación por operación de los órganos de control: estudio de sensibilidad (2014)
Water hammer is a phenomenon that occurs in pressure piping systems, when the flow conditions are suddenly changed by the operation of valves, pumps, turbines or any other element that modifies the energy levels and the flow rate that is applied. moves through the system. It is usually associated with strong pressure changes that produce high levels of noise and damage to the ducts, which are due to the name of the phenomenon.